Methane emissions from contrasting urban freshwaters: Rates, drivers, and a whole‐city footprint. (11th September 2019) - Herrero Ortega, Sonia; Romero González‐Quijano, Clara; Casper, Peter; Singer, Gabriel A.; Gessner, Mark O.
Abstract: Global urbanization trends impose major alterations on surface waters. This includes impacts on ecosystem functioning that can involve feedbacks on climate through changes in rates of greenhouse gas emissions. The combination of high nutrient supply and shallow depth typical of urban freshwaters is particularly conducive to high rates of methane (CH4 ) production and emission, suggesting a potentially important role in the global CH4 cycle. However, there is a lack of comprehensive flux data from diverse urban water bodies, of information on the underlying drivers, and of estimates for whole cities. Based on measurements over four seasons in a total of 32 water bodies in the city of Berlin, Germany, we calculate the total CH4 emission from various types of surface waters of a large city in temperate climate at 2.6 ± 1.7 Gg CH4 /year. The average total emission was 219 ± 490 mg CH4 m −2 day −1 . Water chemical variables were surprisingly poor predictors of total CH4 emissions, and proxies of productivity and oxygen conditions had low explanatory power as well, suggesting a complex combination of factors governing CH4 fluxes from urban surface waters. However, small water bodies (area <1 ha) typically located in urban green spaces were identified as emission hotspots. These results help constrain assessments of CH4 emissions from freshwaters in the world's growing cities, facilitating extrapolation of urban emissions to large areas, including at the global scale. Abstract : The total methane (CH4 ) emission from various types of surface waters of Berlin, Germany, is 2.6 ± 1.7 Gg CH4 /year. CH4 fluxes to atmosphere from urban freshwaters are higher than those from similar pristine water bodies. Urban ponds presented the highest CH4 fluxes.